Exploring pedagogy components used by the lecturer to teach quantity surveying measurement courses: a pilot study - Razali, Atikah; Hussein, Suhailah; Tunku Ahmad, Tunku Badariah; Ibrahim, Mohd Burhan (WMIT Group Sdn Bhd, 2024)
This study is to explore the pedagogical components used by the lecturer to teach Quantity Surveying Measurement Courses (QSMC). According to the literature review, relatively little study has been conducted on the pedagogical components utilised in teaching QSMC, despite the fact that they are critical aspects for successful and efficient instruction. Pedagogical components for teaching QSMC for this study, were adapted from the Herbart theory of five components of pedagogy. Due to the complexity of the QSMC, which creates challenges among the lecturers and learning difficulties among the students, pedagogical components can be proposed as one of the strategies for effective teaching. In order to come up with the pedagogical components framework for teaching QSMC, a semi-structured interview and classroom observation were conducted with a volunteer participant, a QSMC lecturer from Quantity Surveying Higher Education Provider (QS HEP). Based on the findings, there are three most prominent components of pedagogy used for teaching QSMC, namely preparation, presentation, and application. The research findings benefit QSMC lecturers as a reference for a pedagogical foundation framework for teaching QSMC and contribute to the marketability of graduates in the field of Quantity Surveying (QS). It contributes to the development of strategies that suit the needs of the QS learning process.